The complex evolution of Brazilian cotton production - Herbert Klein; Francisco Vidal-Luna (América Latina en la Historia Económica)
Today Brazil is the world’s second leading source of cotton, reprising the role it played for a brief time in the early 19th century. But this history of its production is a complex one of both growth and stagnation, and includes profound changes in the types of cotton exported and where and how it was produced. It went from being a product of small farmers to one grown primarily on large estates. Our essay explores these changes over time and offers an analysis of how production shifted from the Northeast to the Southeast and the ended finally in the Center-West of the country and why it went from a being net importer of cotton to a major exporter in just the past thirty years.